Liver Microbiome in Healthy Rats: The Hidden Inhabitants of Hepatocytes - Xiao Wei Sun; Hua Zhang; Xiao Zhang; Peng Fei Xin; Xue Gao; Hong Rui Li; Cai Yun Zhou; Wen Min Gao; Xuan Xuan Kou; Jian Gang Zhang (Cellular Microbiology, 2023)
The tumor and tissue microbiota of human beings have recently been investigated. Gut permeability is known as a possible resource for the positive detection of tissue bacteria. Herein, we report that microbiota were detected in high abundance in the hepatocytes of healthy rats and that they were shared with the gut microbiota to an extent. We assessed male Sprague Dawley (SD) rats for the 16S ribosomal ribonucleic acid (rRNA) gene. After the rats were sacrificed by blood drainage from the portal vein, we extracted total deoxyribonucleic acid (DNA) from their ileal and colonic contents and liver tissues. The V3–V4 region of the 16S rRNA gene was amplified by polymerase chain reaction (PCR) and sequenced using an Illumina HiSeq 2500 platform. Sequences were assigned taxonomically by the SILVA database. We also detected bacterial lipopolysaccharide (LPS) and lipoteichoic acid (LTA) in situ using immunofluorescence (IF) and western blotting and the 16S rRNA gene using fluorescent in situ hybridization (FISH). In the livers of six rats, we detected 54,867.50±6450.03 effective tags of the 16S rRNA gene and clustered them into 1003 kinds of operational taxonomic units (OTUs; 805.67±70.14, 729–893). Rats showed conservation of bacterial richness, abundance, and evenness. LPS and the 16S rRNA gene were detected in the nuclei of hepatocytes. The main function composition of the genomes of annotated bacteria was correlated with metabolism (79.92±0.24%). Gram negativity was about 1.6 times higher than gram positivity. The liver microbiome was shared with both the small and large intestines but showed significantly higher richness and evenness than the gut microbiome, and the β-diversity results showed that the liver microbiome exhibited significantly higher similarity than the small and large intestines (P<0.05). Our results suggest that the bacteria in the liver microbiome are hidden intracellular inhabitants in healthy rat livers.